Morphological characterisation of selected scyphozoan jellyfish species and geometric morphometric analysis of Chrysaora chinensis in Peninsular Malaysia / Low Liang Boon - Low , Liang Boon (2017)
Although jellyfish blooms have significant impacts to the coastal environments, the effective management of blooms and understanding of their proliferation are often confounded by the lack of baseline data, which includes species identification, their biology and ecology. In Malaysia, jellyfish blooms can negatively impact human activities such as causing beach closures, damage to fishing nets, threats of stings and blocking power station systems. Therefore, detail characterization and documentation of their morphology would facilitate species identification of jellyfish in the field, especially in Malaysian waters and this region which may harbours many undiscovered species. In this study, the morphology of nine jellyfish species found in Peninsular Malaysia that belong to the class Scyphozoa, namely Chrysaora chinensis, Cyanea sp., Versuriga anadyomene, Rhopilema hispidum, Rhopilema esculentum, Phyllorhiza punctata, Acromitus flagellatus, Lobonemoides robustus and Lychnorhiza malayensis were characterised in detail. Sea nettle jellyfish in Malaysia was verified as C. chinensis. The status of Cyanea sp. found in Malaysia is uncertain as it may possibly be a new species. This study also reported the first record of Lychnorhiza malayensis. A total of 107 specimens of C. chinensis were obtained from four coastal areas of Peninsular Malaysia (East-Central, East-North, West-Central, and West-North) to comparecompare compare the possible possible morp hological hological hological hological morphometric analysis. Procrustes superimposition, Principal Component Analysis (PCA) and Canonical Variate Analysis (CVA) were applied to the images of gastrovascular pouches of C.chinensis to extract the shape information. There were no significant differences in shape among all the specimens based on PCA. However, CVA showed shape variation between populations of the four areas of Peninsular Malaysia.